Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.31616/asj.2018.12.5.870
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Radiological Comparison between Three Different Minimally Invasive Surgical Fusion Techniques for Single-Level Lumbar Isthmic and Degenerative Spondylolisthesis: Minimally Invasive Surgical Posterolateral Fusion versus Minimally Invasive Surgical Transforaminal Lumbar Interbody Fusion versus Midline Lumbar Fusion

Abstract: Study DesignRetrospective cohort study.PurposeComparison between three different minimally invasive surgical (MIS) fusion techniques for single-level lumbar spondylolisthesis.Overview of LiteratureThere has been an increase in the development and utilization of MIS techniques for lumbar spine fusion. No study has compared the efficacy of MIS-posterolateral fusion (MIS-PLF), MIS-transforaminal lumbar interbody fusion (MIS-TLIF), and midline lumbar fusion (MIDLF) with modified cortical bone trajectory screws for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 23 publications
1
24
0
Order By: Relevance
“…In staged surgery, patients wore a hard brace, and their activity was restricted to a wheelchair while waiting for the second-stage posterior surgery, which was performed in the prone position a week after the first-stage surgery. In posterior surgery, fixation points were obtained using modified cortical bone trajectory screws, as previously reported [ 20 ]. A posterior column osteotomy (PCO), and additional transforaminal interbody fusion (TLIF) was selected as the corrective technique based on patient characteristics for each case.…”
Section: Methodsmentioning
confidence: 99%
“…In staged surgery, patients wore a hard brace, and their activity was restricted to a wheelchair while waiting for the second-stage posterior surgery, which was performed in the prone position a week after the first-stage surgery. In posterior surgery, fixation points were obtained using modified cortical bone trajectory screws, as previously reported [ 20 ]. A posterior column osteotomy (PCO), and additional transforaminal interbody fusion (TLIF) was selected as the corrective technique based on patient characteristics for each case.…”
Section: Methodsmentioning
confidence: 99%
“…Elmekaty et al [25] compared in a series of 59 patients with single-level lumbar spondylolisthesis MIS-posterolateral fusion, MIS-transforaminal lumbar interbody fusion (MIS-TLIF), and midline lumbar fusion (MIDLF) and concluded that MIDLF to be the least invasive. Furthermore, there was no difference regarding fusion and functional outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Although minimally invasive direct surgical treatments for lumbar spondylolysis have been well described [ 1 3 ] and minimally invasive instrumented fusion techniques are nowadays often selected to treat patients with lumbar spondylolisthesis [ 4 10 ], we believe that the addition in the literature of short illustrative surgical reports specifically addressing the surgical nuances and technical challenges associated with minimally invasive direct pars fracture decompression for isthmic spondylolysis with spondylolisthesis could be of benefit to surgeons in training and surgeons in the early stages of their minimally invasive surgery learning curve. The presence of fibrous pseudo-healing near the fracture line may in fact pose a surgical anatomy challenge that is not seen in degenerative spondylolisthesis, especially if combined to the relatively limited exposure allowed by a tubular approach.…”
Section: Introductionmentioning
confidence: 99%